The influence of physical work environment on employee performance of Dana Usaha Cooperative in Denpasar - Putra, I Made Luhur Adi; Prihastini, Komang Angga; Putri, Ni Made Giana Agastya (goodwood publishing, 2025)
Purpose: The increasingly tight competition among cooperative business employees continues to improve their performance. Employee performance can be improved, one of which is by ensuring a comfortable physical work environment. This study was conducted to determine the influence of the physical work environment and the most dominant variables influencing the performance of employees of the Dana Usaha Cooperative in Denpasar. Research Methodology: This study was conducted at the Sedana Usaha Cooperative. Data collection was carried out through observation data collection techniques, in-depth interviews, and documentation. The study population consisted of 90 employees. The data analysis technique used was the saturated sampling technique or census, which is used if the entire population is used as respondents with the provision that the population is not enough from 100 people. Results: The physical work environment has a positive, significant effect simultaneously and partially on employee performance and has a dominant effect on employee performance at the Dana Usaha Cooperative in Denpasar. Conclusions: Physical Work Environment on Employee Performance has a positive and significant effect simultaneously, a positive and significant effect partially, and a dominant effect on Employee Performance. Limitations: Physical work environment in the form of lighting, air circulation, noise, cleanliness, and work facilities on employee performance measured through a validated questionnaire. Contribution: The results of this study can provide input to leaders to evaluate and implement a good physical work environment so that employee productivity remains good and increases.